MANAJEMEN PENGETAHUAN UNTUK KESELAMATAN PASIEN - Hartono Hartono; Rika Subarniati; Widodo J. Pudjirahardjo; FM. Judajana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Many mistakes are often made in the laboratory such as: confusing results of specimen examination, wrong process of laboratory services and many problems appearing during services can result in patient’s error. The knowledge management can be a systematically way to capture and communicate knowledge to the laboratory technicians in order to minimize errors made in the laboratory. The purpose of this study is to prove that by implementation of patient’s safety using management strategy of knowledge about patient’s safety can increase the performance of laboratory personnel. The study is carried out pre-experimentally by using a pre-post design in a group without a control group comprising 55 respondents. Prior to giving implementation about knowledge of patient’s safety, the study subjects were tested by a pre-test about: the personnel’s potentials (mindset, attitude, awareness and knowledge), quality of work and performance of the personnel. Knowledge management was implemented in several stages, starting from dispersion of knowledge by making: modules, stages of setting up a team, distribution of knowledge by training and executing patient’s safety and acquainting knowledge by routine team meetings, recording, reporting and evaluation of patient’s safety. The increase of potentials, work process quality and personnel performance was post-tested to show a change and implementation effect of knowledge management about patient’s safety. The result showed a significant change in the personnel potentials post implication of knowledge management (p<0.001). A significant change was also shown in increase work quality (p<0.001). The influence of potential increase of work process quality showed a significant correlation (p=0.172, β=01.87). The increase of personnel potentials also influenced the improvement of their performance (p=0.002, β: 0.406). However, the increase of personnel work process quality significantly influenced the improvement of personnel performance (p<0.001, (β=0.581) Based on this study it can be concluded that knowledge management about patient’s safety can influence the increase of potentials and quality of personnel work process. The increase of quality on the personnel work process can significantly influence the improvement of personnel performance as well.